2021
DOI: 10.1111/jgh.15354
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in upper GI endoscopy ‐ current status, challenges and future promise

Abstract: White‐light endoscopy with biopsy is the current gold standard modality for detecting and diagnosing upper gastrointestinal (GI) pathology. However, missed lesions remain a challenge. To overcome interobserver variability and learning curve issues, artificial intelligence (AI) has recently been introduced to assist endoscopists in the detection and diagnosis of upper GI neoplasia. In contrast to AI in colonoscopy, current AI studies for upper GI endoscopy are smaller pilot studies. Researchers currently lack l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…With further advances in technology, we do expect to see significant improvements in the performance of AI surpassing that of the endoscopist, and with the support of AI, it would also help different endoscopists achieve more consistent results. [17][18][19] This study also highlights the potential benefits of AI in augmenting endoscopy. In our study, the AI-based system took almost 20 times faster (677.14 vs 42.02 s) to evaluate and classify the 300 images as compared with the average time taken by the endoscopists.…”
Section: Discussionmentioning
confidence: 66%
“…With further advances in technology, we do expect to see significant improvements in the performance of AI surpassing that of the endoscopist, and with the support of AI, it would also help different endoscopists achieve more consistent results. [17][18][19] This study also highlights the potential benefits of AI in augmenting endoscopy. In our study, the AI-based system took almost 20 times faster (677.14 vs 42.02 s) to evaluate and classify the 300 images as compared with the average time taken by the endoscopists.…”
Section: Discussionmentioning
confidence: 66%
“…Many studies have reported the development of AI models to detect gastric cancer, including our previous study, which showed favorable results [ 2 , 3 , 8 , 9 , 10 , 11 , 12 ]. All studies have used endoscopic static images to train AI models, whereas few have used endoscopic videos to test the AI model.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies trained CNNs to aid early detection in GEA, recently summarized in a meta-analysis that found superiority of applying DL for detection of Barrett’s esophagus [ 132 , 133 , 134 , 135 , 136 , 137 ]. Currently, clinical trials are already investigating its sensitivity and specificity, if applied in a clinical setting, with several studies showing DL models to identify early GEA [ 138 , 139 ].…”
Section: Machine Learning—basic Concepts Specific Applications and Future Directions In Geamentioning
confidence: 99%